COMPOSITION OF CAPTURE CAPTURE RESULTS OF TANCAP PARTS IN HAJORAN VILLAGE, PANDAN DISTRICT, NORTH SUMATERA PROVINCE - simanjuntak, Lisi; Syaifuddin, Syaifuddin; Isnaniah, Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT            This study aims to determine the composition of the catch of the step chart fishing gear that is operated in the Hajoran Village, Pandan District, North Sumatra ProvinceThis research was conducted in May 2019 in the Hajoran Village, Pandan District, Central Tapanuli Regency, North Sumatra Province. The method used in this study is a survey method that is observation by going directly to the field with fishermen to follow the fishing process starting from the process of dropping the fishing gear on the chart to calculate the number of catches at the time of raising the fishing gear on the chart. Data obtained is tabulated and then analyzed descriptively to reach a conclusion.            The data analyzed are the total number of catches (gr) as well as the type and number of catches (tails). In the manufacture of one unit of this step chart fishing gear can take 2-3 weeks and the price of making this one step chart as a whole (whole) and can be directly operated requires a cost of around Rp.75,000,000 to Rp.100,000,000.) the construction of fishing gear in the village of Hajoran consists of building structures, nets (waring), ballast, step on the chart, rollers and lights. And the ships used are 9 m long and 1.5mwide. The engine used on the ship is a Yamaha engine with a power of 15 PK. the most catches are obtained before midnight with a total weight of 170 (kg), a total weight of 490,491 (tails) and catches after midnight 134 (kg) and a total weight of 189,757 (tails).Keywords : Composition; Catch; Step Chart Capture Tool; Hajoran village; North Sumatra.